Assessment of patient safety culture in primary care (Research, Society and Development, 2022)
Objective: To evaluate the patient safety culture among Primary Health Care professionals in a municipality in Triângulo Mineiro region. Methodology: Observational, exploratory study with a quantitative approach. A total of 407 professionals who are part of the teams of the Family Health Strategy of the municipality participated, through the application of the instrument “Medical Office Survey on Patient Safety Culture”, a translated version, adapted and validated for Brazil. Results: The three best-evaluated constructs considered “strengths” of the patient safety culture were “Follow-up of patient care” (90.1%), “Teamwork” (82.6%) and “Exchange of information with other sectors” (82.5). As weaknesses, the constructs “Support from managers in patient safety” (58.2%) and “Open communication” (54.4%) were identified, expressing themselves as areas that need improvement. Only “Work pressure and rhythm” (27.0%) had a negative patient safety culture. Conclusion: Overall, the assessment was positive regarding the patient safety culture on the part of Primary Health Care professionals in the Brazilian municipality. And, with regard to areas that need improvement, it brings to light gaps in health care or management that can weaken the quality of care. Such results favor critical-reflective thinking about the importance of strengthening the theme.